(untitled) (Research, Society and Development, 2024)
Anatomical practices are very old knowledge, which over the centuries have adapted to technological advances. As a result, it is important to make a connection between historical periods and methodological advances in this science. This is an integrative review with a qualitative approach, which used the “PICo” strategy to formulate the guiding question. From this, the descriptors for the research were selected, which was carried out in the MEDLINE, LILACS and Embase databases. This article aims to analyze developments in the study of anatomy over time, portraying the major changes in anatomical practice, through correlation with historical periods and their respective contributions. In this context, after researching the literature, 40 articles were selected for the construction of this study, which describe the history of anatomy, with an emphasis on the technological evolution of this science, as well as its teaching methods throughout history. Given the importance of traditional techniques, such as dissection, for the advancement of anatomy and the evolution of new models for its study, the need for integration of techniques to optimize learning is evident.